Evaluasi Kinerja Pelayanan Kereta Api Bandara Manggarai-Soekarno Hatta Berdasarkan Persepsi Pengguna Jasa - Listifadah Listifadah (Jurnal Penelitian Transportasi Darat, 2020)
ABSTRACT Evaluation of Manggarai-Soekarno Hatta Airport Train Service Performance Based on Users Perception: Initially, the airport train was operated to serve the route from Sudirman Station to Soekarno Hatta Airport. However, since October 5, 2019, PT Railink officially operates the airport train from Manggarai Station to Soekarno-Hatta Station. The existence of the Manggarai-Soekarno Hatta airport train is expected to make it easier for the passanger because Manggarai station is relatively more integrated with other modes of transportation such as the Trans Jakarta and the Indonesian Commuter Train (KCI) from Bogor, Depok and Bekasi. This is expected to increase the occupancy of airport train passengers. In order to attract public interest, it is necessary to evaluate the implementation of the Manggarai-Soekarno Hatta Airport Train in order to support the achievement of optimal services so as to increase the number of users. The purpose of this research is to evaluate the operation of the Manggarai Airport Train-Soekarno Hatta. The purpose of this study is to provide recommendations in order to support the achievement of optimal services so as to attract the public's interest to use them in order to increase the number of users. The analytical method used is the Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results of this study are based on the results of the Paired T-test Sample, it can be concluded that there is a statistically significant difference in the number of daily passengers before and after the operation of the Manggarai Airport Train Station. Therefore, statistically the existence of the Airport Train Station in Manggarai has a significant impact on the daily number of airport train passengers. In addition, what should be improved in terms of services are easily accessible travel information; ease of obtaining tickets; ease of changing to other transportation (integration between modes); the availability of facilities for passengers with special needs both at the station and inside the train. For the airport train user satisfaction index value as stated in the Customer Satisfaction Index (CSI) is 0.8682, which is in the very satisfied category. Keywords: Airport Train: Importance Performance Ananlysis (IPA); Customer Satisfaction Index (CSI). ABSTRAK Kereta bandara pada awal dioperasikan melayani rute Stasiun Sudirman menuju Bandara Soekarno Hatta. Akan tetapi sejak 5 Oktober 2019 PT Railink resmi mengoperasikan kereta api bandara dari Stasiun Manggarai ke Stasiun Soekarno-Hatta. Keberadaan kereta api bandara Manggarai-Soekarno Hatta diharapkan memudahkan masyarakat karena di stasiun Manggarai relatif lebih terintegrasi dengan moda transportasi lain seperti Trans Jakarta maupun Kereta Commuter Indonesia (KCI) dari arah Bogor, Depok maupun Bekasi. Hal tersebut diharapkan dapat meningkatkan okupansi penumpang kereta api bandara. Agar menarik minat masyarakat diperlukan evaluasi penyelenggaraan KA Bandara Manggarai-Soekarno Hatta guna mendukung tercapainya pelayanan yang optimal sehingga dapat dapat meningkatkan jumlah penggunanya. Maksud dari penelitian ini adalah melakukan evaluasi terhadap penyelenggaraan Kereta Api Bandara Manggarai-Soekarno Hatta. Tujuan dari penelitian ini adalah memberikan rekomendasi guna mendukung tercapainya pelayanan yang optimal sehingga dapat menarik minat masyarakat untuk menggunakannya agar dapat meningkatkan jumlah penggunanya. Metode analisis yang digunakan adalah Importance Performance Ananlysis (IPA) dan Customer Satisfaction Index (CSI). Hasil dari penelitian ini adalah berdasarkan hasil Paired T-test Sample dapat disimpulkan bahwa secara statistik terdapat perbedaan yang signifikan jumlah penumpang harian sebelum dan sesudah pengoperasian Stasiun KA Bandara Manggarai. Oleh karena itu, secara statistik keberadaan Stasiun KA Bandara di Manggarai memberikan dampak yang signifikan terhadap jumlah penumpang harian KA Bandara. Selain itu, yang harus ditingkatkan dari segi pelayanan adalah informasi tentang perjalanan yang mudah diakses; kemudahan dalam memperoleh tiket; kemudahan berganti angkutan lain (integrasi antar moda); tersedianya fasilitas bagi penumpamg berkebutuhan khusus baik di stasiun maupun didalam kereta. Untuk nilai indeks kepuasan pengguna KA Bandara yang tertuang dalam Customer Satisfaction Index (CSI) adalah sebesar 0,8682 yaitu dalam kategori sangat puas. Kata Kunci: Kereta Bandara, Importance Performance Ananlysis (IPA); Customer Satisfaction Index (CSI).